Fostering plant protection against certain bacterial diseases through quorum-sensing signal molecules: a critical review - Anwar, Muhammad; Vinothkanna, Annadurai; Jia, Ai-Qun (Frontiers in Plant Science, 2025)
Quorum sensing (QS) and clustered regularly interspaced short palindromic repeats (CRISPR) systems are envisaged as revolutionary in abating plant bacterial pathogens. Bacterial cell–cell communication and plant pathogen QSSMs (quorum sensing signaling molecules) are dissected for underlying mechanisms in prominent pathogens, viz., Pseudomonas syringae, Erwinia amylovora, and Xanthomonas campestris. Biofilm formation and virulence mechanisms are critically addressed to repurpose potential QS inhibition strategies. CRISPR technologies are combined with CRISPR engineering to produce enhanced disease-resistant varieties, with potential applications. QS-CRISPR interplay for deciphering the key interactive changes in plant health management is prioritized for deliberate future research outcomes. Sustainable agricultural practices are envisaged for successful lab-to-field authentic field trials and large-scale applicability across the globe. Potential technical limitations, the need for stringent agricultural laws, and future innovations are addressed. Moreover, the cost-effectiveness, enhanced crop production, yield, and productivity hindering the above key plant bacterial pathogens are comprehensively addressed against these plant bacterial pathogens. Furthermore, a future outlook characterized by extensive outreach and global implications is substantiated regardless of regional specificity, climate change, and global warming. A decade of research on advancements in adequate plant protection is revisited to incorporate augmented approaches, including artificial intelligence (AI) and machine learning, in sustainable agriculture. The significance of the present review is based on addressing QSSMs and plant protection strategies encompassing modern molecular biological techniques.